On the History of an Anecdote - Kostiukhin, Evgenii; Bailey, James; Leary, James P. (FOLKLORICA - Journal of the Slavic, East European, and Eurasian Folklore Association, 2018)
This article explores the historical antecedents to the Russian anecdote which remarks on the reactions by various nationalities’ to finding a fly in their soup and considers the function of such anecdotes in their popular usage.